Defending Francophone and Indigenous Perspectives in Alberta’s Social Studies Curriculum: The Views of 13 Francophone Education Stakeholders - Gani, Raphaël; Scott, David (Alberta Journal of Educational Research)

(untitled) (Faculty of Education, University of Alberta, 2024)
Many social studies teachers have argued that the mandate to distinctively value Francophone and Indigenous perspectives is unjust without similarly valuing other perspectives within Alberta’s K–12 social studies curriculum (Gani, 2022a; Gani & Scott, 2017; Scott & Gani, 2018). Rather than outlining why these two sets of perspectives need to be specifically taught, the current curriculum justifies this mandate based on vague and undefined “historical and constitutional reasons” (Alberta Education, 2005, p. 4). Using an online survey and a focus group interview, Raphaël Gani asked 13 Francophone education stakeholders in Alberta (e.g., teachers, heritage group representatives, education consultants) to justify the distinct attention given to Francophone and Indigenous perspectives in the social studies curriculum. To facilitate this process, participants were asked to respond to quotes from Alberta educators questioning the need to distinctly acknowledge these perspectives. The participants’ responses offered a vision of Canada, a goal for education in Alberta, and a means to achieve this goal. They also offered an original view on the nature of Francophone perspectives, their relationship with Indigenous perspectives, along with how both Francophone and Indigenous perspectives are distinct from the many other diverse perspectives in Alberta today.